2018
DOI: 10.1002/brb3.1144
|View full text |Cite
|
Sign up to set email alerts
|

Moderating effect of mode of delivery on the genetics of intelligence: Explorative genome‐wide analyses in ALSPAC

Abstract: IntroductionIntelligence is a core construct of individual differences in cognitive abilities and a strong predictor of important life outcomes. Within recent years, rates of cesarean section have substantially increased globally, though little is known about its effect on neurodevelopmental trajectories. Thus, we aimed to investigate the influence of delivery by cesarean section on the genetics of intelligence in children.MethodsParticipants were recruited through the Avon Longitudinal Study of Parents and Ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 125 publications
(164 reference statements)
0
5
0
Order By: Relevance
“…As we note in Section 2, fluid intelligence is the ability to use logical reasoning to solve new problems, while crystallized intelligence includes acquired knowledge and verbal skills (e.g., Carpenter et al, 1990). WISC-III captures both fluid intelligence (Dickson et al, 2016) and crystallized intelligence (Smajlagić et al, 2018). The WISC-III Full Scale IQ score is based on ten subtests: information; similarities; arithmetic; vocabulary; comprehension; picture completion; coding; picture arrangement; block design; and object assembly.…”
Section: Theory-of-mind Test: Diagnostic Analysis Of Nonverbal Accuracymentioning
confidence: 99%
“…As we note in Section 2, fluid intelligence is the ability to use logical reasoning to solve new problems, while crystallized intelligence includes acquired knowledge and verbal skills (e.g., Carpenter et al, 1990). WISC-III captures both fluid intelligence (Dickson et al, 2016) and crystallized intelligence (Smajlagić et al, 2018). The WISC-III Full Scale IQ score is based on ten subtests: information; similarities; arithmetic; vocabulary; comprehension; picture completion; coding; picture arrangement; block design; and object assembly.…”
Section: Theory-of-mind Test: Diagnostic Analysis Of Nonverbal Accuracymentioning
confidence: 99%
“…A total of 400 CpG sites were selected from 6 EWAS [ 26 , 45 , 46 , 47 , 48 , 49 ]. Additionally, a total of 31,981 CpG sites were selected, which were annotated to 835 genes reported from 13 GWAS after excluding duplicate genes [ 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 ]. As a result, 8743 CpG sites were finally selected ( Tables S2 and S3 ).…”
Section: Resultsmentioning
confidence: 99%
“…Curran et al [ 31 ] assessed the school performance in Swedish adolescents with 1,036,424 children born by unassisted vaginal delivery and 42,107 by elective cesarean section and found poor school performance was observed more in adolescents with cesarean-section birth. The method of delivery may moderate the genetic disposition (rs705670 on chromosome 9) of PIQ in children [ 16 ]. The rs705670 on chromosome 9 for PIQ, LINC01502 , have recently been implicated in several neuropsychiatric disorders where IQ is affected, such as ADHD [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, other research showed no association between cesarean deliveries with better cognitive development in children [ 15 ]. A recent study revealed that mode of delivery can moderate the genetics of intelligence based on an explorative genome-wide analysis [ 16 ]. There is an urgent need for further studies that may increase our understanding of effects of delivery modes on intelligence in children.…”
Section: Introductionmentioning
confidence: 99%